Relathionship of Self Confidence and Academic Procrastination Students S1 Guidance and Counseling FIP UNP - Nela Reska; Taufik Taufik (Jurnal Neo Konseling, 2019)
Academic Procrastination is one's job to replace his tasks or work which causes failure to complete tasks / work on time. The fact that is found still increases students' academic procrastination. One of the factors that influence academic procrastination is self-confidence. This study aims to (1) Describe the level of self-confidence of S1 BK FIP UNP students (2) Describe the level of academic procrastination of S1 BK FIP UNP students (3) Test the level of significance of the relationship between student confidence with the academic proclamation of S1 BK FIP UNP students. This study uses quantitative research with a descriptive correlational type. The population of the study was 799 students of S1 BK FIP UNP and a sample of 266 students were selected by stratified random sampling. The instruments used are the scale of academic procrastination and self-confidence scale. Analysis of data with descriptive techniques and Pearson Product Moment techniques with the help of the SPSS program for windows 20.00. The research findings explain that: (1) the level of academic procrastination of students on average in the medium category with a percentage of 45.9% (2) the level of student confidence average in the high category with a percentage of 56.4% (3) there is a significant negative relationship between self-confidence and academic procrastination of S1 BK FIP UNP students with a coefficient of -0.213 and a significance level of 0,000 high hopes of confidence, the faster the academic procrastination college student. The lower the confidence, the higher the academic procrastination of students. It is undeniable that there is a significant negative relationship between self-confidence and academic procrastination of S1 BK FIP UNP students.